Association of neutropenia at disease onset with severe surgical necrotizing enterocolitis and higher mortality: A retrospective study - Qin, Fanyue; Yuan, Mengjie; Zhang, Chen; Zhu, Chu; Dong, Huifang; Xu, Falin (Frontiers in Surgery, 2022)
Background Neutrophils are among the earliest immune cells recruited to the site of an intestinal injury, but their predictive role in the progression of necrotizing enterocolitis (NEC) has not been fully elucidated. This study aimed to evaluate if a reduction in neutrophils at the onset of NEC is associated with severe surgical NEC and/or NEC-associated deaths. Methods This is a retrospective cohort study in which neonates underwent surgery due to NEC during 2015–2020. The data on absolute neutrophil count (ANC), before and at the onset of NEC, were collected from the complete blood count results. The primary exposure was the difference in absolute neutrophil count (ΔANC) at NEC onset. The primary outcome was severe surgical NEC, defined as the residual small bowel length after intestinal resection of <30 cm. Results A total of 157 neonates were included in this study, of which 53 were diagnosed with severe surgical NEC. A decrease in ANC at the onset of NEC was associated with an increased probability of severe surgical NEC (crude odds ratio [OR] 1.248, 95% CI 1.107–1.407; P = 0.000). ΔANC (area under the curve [AUC] 0.729, 95% CI 0.653–0.797; P < 0.001] was a good predictor for severe surgical NEC. The addition of platelets to ΔANC at NEC onset (AUC 0.738, 95% CI 0.662–0.808; P < 0.001) resulted in a higher AUC and specificity for severe surgical NEC prediction than ΔANC alone. A reduction in the neutrophil count at NEC onset (ΔANC > 0) was associated with adverse outcomes (hazard ratio [HR] 3.48, 95% CI 1.64–7.36) and a lower survival probability (χ2 10.63; P < 0.001). Conclusion A reduction in the ANC at the onset of NEC was associated with severe surgical NEC and higher mortality. The addition of platelets to ΔANC at NEC onset resulted in a higher predictive value of severe surgical NEC. This study may provide a new insight into the bedside evaluation of NEC by analyzing data from the day of NEC onset.